PythonRobotics: a Python code collection of robotics algorithms - Sakai, Atsushi; Ingram, Daniel; Dinius, Joseph; Chawla, Karan; Raffin, Antonin; Paques, Alexis (2018)
This paper describes an Open Source Software (OSS) project: PythonRobotics. This is a collection of robotics algorithms implemented in the Python programming language. The focus of the project is on autonomous navigation, and the goal is for beginners in robotics to understand the basic ideas behind each algorithm. In this project, the algorithms which are practical and widely used in both academia and industry are selected. Each sample code is written in Python3 and only depends on some standard modules for readability and ease of use. It includes intuitive animations to understand the behavior of the simulation.